2010
DOI: 10.1053/j.ajkd.2010.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Kidney Involvement in Lymphoma: A Case Report and Review of the Literature

Abstract: Kidney involvement is an under-recognized complication of both Hodgkin and non-Hodgkin lymphoma 1. The diversity of lymphoma-related renal manifestations makes diagnosis difficult: while abrupt worsening of kidney function may be the first sign of malignant disease, renal effects can be subtle or even silent. The etiologies of renal involvement are similarly varied. Here we discuss a case of non-Hodgkin lymphoma and associated kidney failure from several distinct malignancy-related mechanisms. We then take the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 29 publications
4
45
0
Order By: Relevance
“…Lymphomatous infiltration of the kidneys (LIK) is relatively common and an underrecognized complication of hematologic malignancies, although it is usually subclinical (21). Approximately one-half of patients with non-Hodgkins lymphoma develop extranodal disease, and the largest case series to date found that 34% of lymphoma patients had parenchymal kidney invasion but only 14% had been diagnosed before death (22).…”
Section: Intrinsic Causesmentioning
confidence: 99%
“…Lymphomatous infiltration of the kidneys (LIK) is relatively common and an underrecognized complication of hematologic malignancies, although it is usually subclinical (21). Approximately one-half of patients with non-Hodgkins lymphoma develop extranodal disease, and the largest case series to date found that 34% of lymphoma patients had parenchymal kidney invasion but only 14% had been diagnosed before death (22).…”
Section: Intrinsic Causesmentioning
confidence: 99%
“…[2] However, as the biopsy is performed infrequently in lymphoma patients, it is likely that the involvement of kidneys in lymphoma patients is overlooked. In a large case series of autopsies performed on lymphoma patients, 34% showed signs of parenchymal invasion, but only 14% had been diagnosed with lymphocytic infiltration of kidneys before the time of death.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, MPGN may present in association with cryoglobulinemia or monoclonal gammopathy [5,7]. Other histopathology previously reported includes minimal change disease [4,8], mesangial proliferative IgA nephropathy [9,10] and membranous nephropathy [3,11]. Concurrent glomerulonephritis and direct infiltration of the kidneys by lymphocytic neoplasms has been reported as well, and the pattern of glomerular injury is similar, showing features of MPGN, membranous nephropathy or paraprotein deposition disease [3,4,12].…”
Section: Discussionmentioning
confidence: 99%
“…Other histopathology previously reported includes minimal change disease [4,8], mesangial proliferative IgA nephropathy [9,10] and membranous nephropathy [3,11]. Concurrent glomerulonephritis and direct infiltration of the kidneys by lymphocytic neoplasms has been reported as well, and the pattern of glomerular injury is similar, showing features of MPGN, membranous nephropathy or paraprotein deposition disease [3,4,12]. In one series, Kowalewska et al showed that 10 (55%) out of 18 patients with renal biopsies demonstrating infiltration of parenchyma by lymphoplasmocytic neoplasms revealed co-existent glomerular injury and suggested that the prevalence of significant glomerulonephritis in this setting may be greater than previously appreciated [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation